Amazon and Walmart on collision course - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 2018)
The case describes how Amazon and Walmart have been two of the most successful retailers in history and responsible for changing the rules of the game in the retail industry. In their wake, they have driven many retailers out of business while transforming how suppliers manage their relationship with powerful retailers. They have both been widely admired even if the market currently views Amazon as having greater potential. The unique trajectory of each retailer, Amazon through online and Walmart through offline, has endowed these companies with different and distinctive capabilities. For the most part they have managed to avoid each other in the competitive marketplace by serving different consumer needs. However, as consumers and markets have been increasingly demanding an omni-channel presence, both retailers have been forced to invade the other’s turf - with Amazon seeking an offline presence and Walmart seeking a substantial online operation. This leads to several questions that engage students. To grow, how should the two retailers confront each other and build their omni-channel operations? What has been their past success in the playing field of their nemesis (Amazon offline and Walmart online)? How does the marketing strategy of the two retailers differ? What are the distinctive capabilities of each retailer and how do these either help or hinder their ability to effectively evolve for an omni-channel future? What are the financial implications of the omni-channel transformation for each retailer? The case is appropriate for courses related to general management, industry analysis, strategy, operations, retailing, marketing, digital, and ecommerce. Students will be able to understand and analyse the complexities involved in online versus offline retail channels, the distinctive capabilities and resources required for each business model, and the challenges faced in developing an omni-channel presence.